APPLICATION OF GAME THEORY FOR DYNAMIC PRICING IN E-COMMERCE - Catalina Edison, Felicia
Game theory is a branch of mathematics that studies models of strategic interaction between rational agents, playing an important role in various fields of science. Dynamic pricing is a flexible pricing strategy that adjusts to changes in market demand in real-time to optimize revenue. Dynamic pricing in e-commerce is a process based on choices made by sellers based on various factors. Therefore, it can be viewed as an interaction between rational agents making decisions, with these rational agents being the sellers. The interaction between sellers who set, lower, or raise prices and buyers who decide to buy now, wait, or switch to competitors reflects the dynamic strategy game. Dynamic pricing algorithms analyze market demand, supply in the market, and competitor prices to determine the optimal price. This study aims to find a way to define dynamic pricing in e-commerce using concepts found in game theory from the perspective of pricing by sellers. Additionally, it will describe game theory concepts that can illustrate the interaction between sellers and buyers in e-commerce. Keywords: game theory, dynamic pricing, e-